2021
DOI: 10.1029/2020tc006355
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the African Plate 75 Ma: From Plate Kinematic Reconstructions to Intraplate Paleo‐Stresses

Abstract: Plate reconstruction studies show that the Neotethys Ocean was closing due to the convergence of Africa and Eurasia toward the end of the Cretaceous. The period around 75 Ma reflects the onset of continental collision between the two plates as convergence continued to be taken up mostly by subduction of the Neotethys slab beneath Eurasia. The Owen transform plate boundary in the northeast accommodated the fast northward motion of the Indian plate relative to the African plate. The rest of the plate was surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…Key observations that can help constrain the torque balance relate to plate kinematics (velocities), intra-plate stress patterns, as well as changes in these quantities over time (Forsyth and Uyeda, 1975;Becker and O'Connell, 2001;England and Molnar, 2022). Several studies, both global and regional in extent, concluded that slab buoyancy is largely balanced by deep resistance, with slab pull reduction factors of ∼ 10 % (Forsyth and Uyeda, 1975;Wortel et al, 1991;Copley et al, 2010;England and Molnar, 2022;Wouters et al, 2021). In contrast, global-scale velocity modelling has favored high net slab pull (reduction factors ≥ 50 %) (Conrad and Lithgow-Bertelloni, 2002;van Summeren et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Key observations that can help constrain the torque balance relate to plate kinematics (velocities), intra-plate stress patterns, as well as changes in these quantities over time (Forsyth and Uyeda, 1975;Becker and O'Connell, 2001;England and Molnar, 2022). Several studies, both global and regional in extent, concluded that slab buoyancy is largely balanced by deep resistance, with slab pull reduction factors of ∼ 10 % (Forsyth and Uyeda, 1975;Wortel et al, 1991;Copley et al, 2010;England and Molnar, 2022;Wouters et al, 2021). In contrast, global-scale velocity modelling has favored high net slab pull (reduction factors ≥ 50 %) (Conrad and Lithgow-Bertelloni, 2002;van Summeren et al, 2012).…”
Section: Introductionmentioning
confidence: 99%